Gneiss domes of the Danba Metamorphic Complex, Songpan Ganze, eastern Tibet. (1st June 2017) - Billerot, Audrey; Duchene, Stéphanie; Vanderhaeghe, Olivier; de Sigoyer, Julia
Graphical abstract: Highlights: Danba Metamorphic Complex (DMC) exhumation due to extrusion. Correspondence between isograds and isotherms shown by field data and thermometry. Isograds and isotherms are folded during the extrusion deformation event. Extrusion of deep hot material induces heat advection in the DMC surrounding rocks. Presence of three kind of gneiss domes explained by long term structural inheritance. Abstract: In this paper we address the formation and exhumation of the Danba Metamorphic Complex (DMC) that represents the deepest structural level of the Songpan Ganze terrane situated along the eastern margin of the Tibetan plateau. The DMC comprises a variety of gneiss domes and offers a unique opportunity to decipher their development during orogenic evolution. For that purpose, PTtD paths of metamorphic rocks sampled at different structural levels have been reconstructed. The DMC is composed of Triassic metaturbidites of the Xikang group, Paleozoic metasedimentary cover and basement of the Yangtze craton. The DMC is structurally marked by transposition of the upright S1 foliation of the Triassic metaturbidites into a NW-SE trending S2 composite foliation dipping to the NE. Transposition is associated with a localized top-to-the-northeast shear zone along the northeastern edge of the DMC and with pervasive top-to-the-southwest shearing from the core to the border of the complex. These structures are consistent with extrusion of the core of the DMC relative to the lower grade Triassic metaturbidites. The position of the biotite isograd overlapping the structural boundary of the DMC suggests that the Triassic metaturbidites have been affected by an increase in temperature as a result of extrusion. Within the DMC, the position of the metamorphic index minerals relative to the composite S2 foliation reveals that biotite, garnet, staurolite and kyanite grew before the transposition into S2, in contrast with sillimanite which crystallizes in the hinge of F2 folds and along the axial planar S2 schistosity. The sillimanite isograd delineates regional-scale overturned F2 folds and cross-cuts the staurolite and kyanite isograds consistent with an increase in temperature during D2 . The melt-in isograd characterizes the deepest structural level of the DMC. PT conditions for these metamorphic rocks, determined using pseudosections and conventional thermometry, indicate a temperature increase from 400 °C to more than 600 °C from the edge to the core of the DMC for a relatively homogeneous pressure ranging from 5 to 6.5 kbar suggesting that isograds and isotherms represent the syn-D2 thermal structure of the orogenic crust. Migmatites exposed in the deepest structural level of the DMC yield a pressure significantly lower than the surrounding metamorphic rock suggesting that they crystallized after D2 and after some exhumation of their hosts. Three different types of gneiss domes are distinguished on the basis of their position relative to the isograds, their structural characteristics, and their position relative to the margin of the Yangtze craton. Close to the craton and at the highest structural level, the Gezong dome represents a basement-rooted tectonic slice, in an intermediate position, the Gongcai dome corresponds to a basement-cored nappe, and further away and at the deepest structural level, the Bawang, Cunuchan and Qingaling domes are migmatite-cored domes. The presence at the current-day surface of this variety of gneiss domes reflects the difference in burial of the margin during the Mesozoic Indosinian orogeny.